N-Alkyl nitrones as substrates for access to N-aryl isoxazolidines via a catalyst-free one-pot three-component reaction with nitroso compounds and olefins. Issue 14 (19th May 2021) - Zhai, Pingan; Li, Wenhui; Lin, Jianying; Huang, Shuangping; Gao, Wenchao; Li, Xing
Abstract : N -Alkyl nitrones are used as starting materials to construct N -aryl isoxazolidines, instead of N -alkyl isoxazolidines or N –H 1, 3-oxazinanes via a catalyst-free one-pot three-component reaction with nitrosoarenes and olefins. Abstract : N -Alkyl nitrones are used as the starting materials to construct various N -aryl isoxazolidines, instead of N -alkyl isoxazolidines or N –H 1, 3-oxazinanes via a catalyst-free one-pot three-component reaction with nitroso compounds and olefins. The mechanism investigations indicate that the in situ formation of N -aryl nitrones from the reaction of N -alkyl nitrones and nitrosoarenes is the key step. The protocol features broad substrate scope, good to excellent chemo-, regio- and diastereo-selectivities, and moderate to excellent yields for most substrates.